2006
DOI: 10.1128/jcm.44.5.1853-1855.2006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Commercial Latex Agglutination Assay for Serological Diagnosis of Leptospirosis

Abstract: Leptospirosis is a febrile zoonosis of worldwide distribution. A latex agglutination assay was evaluated in two studies, the first using a panel of well-characterized sera from patients with leptospirosis and from patients with other disease states and the second, a prospective hospital-based study, evaluating sera from 186 consecutive patients admitted to hospital with acute febrile illness. The confirmed leptospirosis serum panel included paired acute-and convalescent-phase specimens from 40 cases, of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…[1][2][3] The sensitivity of these tests ranges from 88-100% and specificity from 95-99.8%. [1,8,9] Gupta et al, have reported sensitivity of IHA to be 100% and specificity 94% as compared to MAT. [10] LeptoTek Dri-dot assay has shown an overall sensitivity of 90% and specificity of 92%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The sensitivity of these tests ranges from 88-100% and specificity from 95-99.8%. [1,8,9] Gupta et al, have reported sensitivity of IHA to be 100% and specificity 94% as compared to MAT. [10] LeptoTek Dri-dot assay has shown an overall sensitivity of 90% and specificity of 92%.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Traditionally considered an occupational risk among persons exposed to contaminated water or infected animal urine, it is becoming recognized as a major public health problem, particularly in the tropics. [2,3] In tropical and subtropical regions, the disease is endemic and exposure is widespread.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the broad spectrum of symptoms, the disease largely remains underdiagnosed. If it is not treated in due course, patients may develop renal damage or liver failure, and in some cases death may occur (2,5,22). Although leptospirosis can be treated, early diagnosis is critical for the establishment of effective antibiotic therapy.…”
mentioning
confidence: 99%
“…These assays have been used as alternatives to MAT but have low sensitivity especially during the acute phase (Smits et al, 2001;Effler et al, 2002;Hull-Jackson et al, 2006;McBride et al, 2007). Furthermore, the diagnostic accuracies of these techniques are poor in some areas where leptospirosis is endemic (Blacksell et al, 2006;Myint et al, 2007).…”
Section: Laboratory Diagnosismentioning
confidence: 99%